Mobilising connections with art: Artcasting and the digital articulation of visitor engagement with cultural heritage. Issue 4 (3rd April 2019) - Ross, Jen; Knox, Jeremy; Sowton, Claire; Speed, Chris
ABSTRACT: This article offers insights into how digital methods in cultural heritage settings can help evoke and illuminate the richness of visitor engagement and interpretation, especially in relation to expressions of ownership. Drawing on the Artcasting research project, which examined how galleries can inventively evaluate visitors' engagement with art, we propose that, in addition to looking for commonalities and stability in visitors' articulation of engagement, it is beneficial to look for ways to make sense of difference. The project drew on theories of mobility to explore visitor engagement with cultural heritage, creating an artcasting platform that invited visitors to 'cast' artworks to another place or time. We analyse artcasting data through two 'movements'. The first uses thematic analysis of artcasts to show how visitors to two ARTIST ROOMS exhibitions expressed ownership in relation to their engagement with artworks. The second demonstrates how individual responses can be put into relationship and understood as an articulation of engagement that moves beyond the interpretive authority of the gallery or any one visitor. The article contributes new perspectives to understandings of articulation and engagement and their relationship to the production of heritage, and reflects on implications for moving digital practice towards more complexity and diversity.